Facilitating pain assessment and communication in people with deafness: a systematic review - Irene Mansutti; Catarina Tomé-Pires; Stefania Chiappinotto; Alvisa Palese (BMC, 2023)
Abstract Background Pain is a common reason for seeking out healthcare professionals and support services. However, certain populations, such as people with deafness, may encounter difficulties in effectively communicating their pain; on the other side, health care professionals may also encounter challenges to assess pain in this specific population. Aims To describe (a) the state of the research in the field of pain assessment in individuals with deafness; (b) instruments validated; and (b) strategies facilitating the pain communication or assessment in this population. Methods A systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were performed, searching Medline, CINAHL, Scopus, Embase and PsycInfo databases, from their initiation to July 2023. Primary and secondary studies, involving adults with deafness and investigating pain assessment and communication difficulties, facilitators, or barriers, were eligible. The included studies were assessed in their methodological quality with the Quality Assessment for Diverse Studies tool; data extraction and the narrative synthesis was provided by two researchers. Results Five studies were included. Two were validation studies, while the remaining were a case report, a case study and a qualitative study. The interRAI Community Health Assessment and the Deafblind Supplement scale have been validated among people with deafness by reporting few psychometric properties; in contrast, instruments well established in the general population (e.g. Visual Analogue Scale) have been assessed in their usability and understandability among individuals with deafness, suggesting their limitations. Some strategies have been documented as facilitating pain communication and assessment: (a) ensuring inclusiveness (the presence of family members as mediators); (b) ensuring the preparedness of healthcare professionals (e.g. in sign language); and (c) making the environment friendly to this population (e.g. removing masks). Conclusions The research regarding pain in this population is in its infancy, resulting in limited evidence. In recommending more research capable of establishing the best pain assessment instrument, some strategies emerged for assessing pain in which the minimum standards of care required to offer to this vulnerable population should be considered.